Lightning Fast Animation in Element 3D : master the intricacies of Element 3D, the fast-rendering Adobe After Effects plugin - Audronis, Ty (Community experience distilled, 2014)
In Detail Element 3D is a plugin for Adobe After Effects, used to create basic, yet stunning 3D visual effects. Some may find 3D to be tricky and downright complex. Element 3D allows actual 3D models to be created from scratch or exported to Adobe After Effects, and rendered and composited at a high level of quality and impressive speed. This practical guide will lift the veil of mystery around 3D animation. It will teach you everything from modeling, preparing, and exporting from various 3D programs to match-motion, texturing, and complex animations using Element 3D. This book is a comprehensive guide to using Element 3D and is appropriate for users of all levels. It will walk you through the basics of modeling objects for Element 3D. Then, you'll learn how to texture, light, and animate as well as optimize your scenes for quick render times. You will discover some of the limits of Element 3D, and learn how to break through those barriers to create virtually any 3D scene imaginable. You will also learn how to take advantage of other 3D programs such as Maya and Blender to create content and create stunning abstract scenes in relatively no time, and how to composite 3D animation into motion-tracked live action scenes. By the time you complete this book, you will have all the information you need to effectively create professional 3D graphics using Element 3D. Approach An easy-to-follow and all-inclusive guide, in which the underlying principles of 3D animation as well as their importance are explained in detail. The lessons are designed to teach you how to think of 3D animation in such a way that you can troubleshoot any problem, or animate any scene that comes your way. Who this book is for If you are a Digital Artist, Animation Artist, or a Game Programmer and you want to become an expert in Element 3D, this is the book for you. Although there are a lot of basics for beginners in this book, it includes some advanced techniques for both animating in Element 3D, and overcoming its limitations. A basic working knowledge of Adobe After Effects is needed.